Neighbor Discovery Message as Threats on 6to4 Tunneling - Bahaman, Nazrulazhar; Anton Satria, Prabuwono; Zakaria, Nurul Azma (2014 Academic Journal Inc., 2014)
The 6to4 tunneling is a type of automatic tunneling that developed among other numerous of transition mechanisms. It was introduced to ensure smooth implementation of IPv6 on existing network. However, it is believed that the implementation has been manipulated to execute several types of attacks. As a concern, this study thoroughly describes on potential of Neighbor Discovery based attack passed through 6to4 Tunneling. The preference development tools and networking mechanism suite are setup to conduct proposed attack method under testbed environment. The results carried out proved that the attacking method is feasible to attempt, while 6-4 tunnel showed the influence on the achievement of this attack in current internet.